2022
DOI: 10.17159/2078-516x/2022/v34i1a15259
|View full text |Cite
|
Sign up to set email alerts
|

SA Rugby Injury and Illness Surveillance and Prevention Project (SARIISPP): The Carling Currie Cup Premiership Competition Injury Surveillance Report 2021

Abstract: The content of the report is based on data collected by the SA Rugby Injury and Illness Surveillance and Prevention Project (SARIISPP) steering group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been shown in previous studies that teams with lower injury rates had more success in the Currie Cup competition [6,7]. It has also been shown that injury burden needs to be considered for success and not simply injury rates alone [8]. Teams who fall in the green zone (below average and 95%CI), will generally not be impacted as much by their injury burden, regardless of whether their injury rate or average severity is relatively high.…”
Section: Overall Severitymentioning
confidence: 97%
“…It has been shown in previous studies that teams with lower injury rates had more success in the Currie Cup competition [6,7]. It has also been shown that injury burden needs to be considered for success and not simply injury rates alone [8]. Teams who fall in the green zone (below average and 95%CI), will generally not be impacted as much by their injury burden, regardless of whether their injury rate or average severity is relatively high.…”
Section: Overall Severitymentioning
confidence: 97%